Treatment of acute Nipah encephalitis with ribavirin - Chong, H.T.; Kamarulzaman, A.; Tan, C.T.; Goh, K.J.; Thayaparan, T.; Kunjapan, R.; Chew, N.K.; Chua, K.B.; Lam, S.K. (2001)
Nipah virus, a newly identified paramyxovirus caused a severe outbreak of encephalitis in Malaysia with high fatalities. We report an open-label trial of ribavirin in 140 patients, with 54 patients who were managed prior to the availability of ribavirin or refused treatment as control. There were 45 deaths (32) in the ribavirin arm; 29 deaths (54) occurred in the control arm. This represents a 36 reduction in mortality (p = 0.011). There was no associated serious side effect. This study suggests that ribavirin is able to reduce the mortality of acute Nipah encephalitis.